2021
DOI: 10.1016/j.annemergmed.2021.05.026
|View full text |Cite
|
Sign up to set email alerts
|

The Rapid Evaluation of COVID-19 Vaccination in Emergency Departments for Underserved Patients Study

Abstract: Objectives Emergency departments (EDs) often serve vulnerable populations who may lack primary care and have suffered disproportionate COVID-19 pandemic effects. Comparing patients having and lacking a regular source of medical care and other ED patient characteristics, we assessed COVID-19 vaccine hesitancy, reasons for not wanting the vaccine, perceived access to vaccine sites and willingness to get the vaccine as part of ED care. Methods Cross sectional survey conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 40 publications
0
57
1
Order By: Relevance
“…Although it is not possible to fully ascertain the mechanisms behind this lagged vaccination coverage from the study findings alone, past work has identified a range of hesitancy factors related to obtaining vaccination in people experiencing homelessness, including fear or mistrust of the vaccine, misinformation spread in media, uncertainties about personal risk of COVID-19, and elements related to access to health-care structures and trust within the patient–provider relationship. 21 , 23 , 24 , 31 , 32 Furthermore, systematic structural barriers commonly faced by people experiencing homelessness 33 possibly also acted as obstacles to COVID-19 vaccination in the study population. For instance, during the study period, many of the centralised provincial vaccination clinics required advanced scheduling of appointments through online websites or portals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is not possible to fully ascertain the mechanisms behind this lagged vaccination coverage from the study findings alone, past work has identified a range of hesitancy factors related to obtaining vaccination in people experiencing homelessness, including fear or mistrust of the vaccine, misinformation spread in media, uncertainties about personal risk of COVID-19, and elements related to access to health-care structures and trust within the patient–provider relationship. 21 , 23 , 24 , 31 , 32 Furthermore, systematic structural barriers commonly faced by people experiencing homelessness 33 possibly also acted as obstacles to COVID-19 vaccination in the study population. For instance, during the study period, many of the centralised provincial vaccination clinics required advanced scheduling of appointments through online websites or portals.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained various sociodemographic, health-care usage, and clinical characteristics available in the health-care administrative databases that were found to previously be associated with vaccine uptake in people experiencing homelessness, identified as barriers to accessing and accepting COVID-19 vaccines in people experiencing homelessness or aligned with domains of the WHO 3C model for the determinants of vaccine hesitancy. 21 , 22 , 23 , 24 , 25 Characteristics and variable definitions are detailed in appendix 2 (p 18 ).…”
Section: Methodsmentioning
confidence: 99%
“… Fridman et al, 2021 , Teherani et al, 2021 , Akel et al, 2021 , Romer and Jamieson, 2021 , Keene Woods et al, 2021 , Ma and Ma, 2021 , Roberts et al, 2021 , Mondal et al, 2021 , Patil et al, 2021 , Rabin and Dutra, 2021 , Olanipekun et al, 2021 , Okoro et al, 2021 , Johnson et al, 2021 , Jacob et al, 2021 , Carson et al, 2021 , Bogart et al, 2021 , Rodriguez et al, 2021 , Ciardi et al, 2021 , Savoia et al, 2021 , Ofei-Dodoo et al, 2021 , Zheng et al, 2021 , Sharma et al, 2021 , Baniak et al, 2021 , Geana et al, 2021 , Hirshberg et al, 2021 , Rungkitwattanakul et al, 2021 .…”
Section: Uncited Referencesmentioning
confidence: 99%
“…Recent literature also highlights increased attention to rapid research and evaluations in emergency contexts ( Rodriguez et al, 2021 ). Rapid approaches can provide contextually rich information on behaviours influencing service use.…”
Section: Rapid Evaluation Methodsmentioning
confidence: 99%
“…Lessons can be drawn from previous infectious disease outbreaks such as Ebola in West Africa in 2014-2015 which necessitated rapid responses to facilitate control, treatment and prevention. An evaluation of UNICEF's Response to the Ebola Outbreak highlighted that rapid response strategies in health emergency contexts should be evidence-based and utilise robust data on the evolution of practice over time and on community knowledge, attitudes and perceptions (UNICEF, 2016) Recent literature also highlights increased attention to rapid research and evaluations in emergency contexts (Rodriguez et al, 2021). Rapid approaches can provide contextually rich information on behaviours influencing service use.…”
Section: Use Of Rapid Approaches In Public Health Emergency Contextsmentioning
confidence: 99%